Employer Preferences Towards Recruitment of Refugees – A Danish Vignette Study - Rasmus Lind Ravn; Thomas Bredgaard (Nordic Journal of Migration Research, 2021)
Refugees have higher unemployment rates, lower employment rates and are more often in precarious employment compared to native Danes. In fact, the employment rate of people with a refugee background never reaches that of those born in Denmark. In this article, we examine the preferences of Danish employers in recruiting jobseekers with a refugee background and test how different country backgrounds impact recruitment preferences. We use a vignette experiment with descriptions of fictitious job applicants to explore whether a ‘refugee migrant penalty’ exists on the Danish labour market. We find that workplaces evaluate refugee jobseekers less positively than native jobseekers and that an additional country penalty exists for Ethiopian jobseekers compared to refugees with no country of origin specified. We interpret this as evidence that refugee jobseekers will face a disadvantage when competing for jobs with the native population.